Manual for gender mainstreaming : employment, social inclusion and social protection policies - (:unkn) unknown (Office for Official Publications of the European Communities, 2008)
Die Publikation zeigt Wege zur Implementierung von Gender Mainstreaming-Vorgaben der EU-Kommission in die Arbeitsmarktpolitik auf. (BIBB-Doku)
Keywords: G 2.4.5 Gender Mainstreaming; G 1.2 Arbeitsmarkt; I 2.2 Europa; Gleichberechtigung; Chancengleichheit; Gleichstellungspolitik; Gender Mainstreaming; Arbeitsmarktpolitik; Europa; Quantitative Angaben